Real life use of prostacyclin analog (iloprost), a multi-centric survey data from the Scleroderma study group Emilia Romagna (Sclero-RER) and review of the literature. - Magnani, Luca; Ariani, Alarico; Lo Monaco, Andrea; Girelli, Francesco; Spinella, Amelia; Lumetti, Federica; Reta, Massimo; Arrigoni, Eugenio; Ursini, Francesco; Bezzi, Alessandra; Cataleta, Pierluigi; Montaguti, Luca; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Iloprost is recommend worldwide for the treatment of RP and the healing of DUs. The aim of this study is to report the regimens of Iloprost administered in different rheumatological centers within the same regional Health System Methods: A questionnaire exploring different items related to the use of Iloprost was developed and reviewed by three expert rheumatologists. The questionnaire was distributed as an online survey to all local SSc referral centers in Emilia-Romagna (Italy). Data are reported as percentage or median with interquartile range (IQR), as appropriate. An updated review of world literature on this topic was also carried out. Results: All the invited centers completed the survey. There were both local (8) and university hospitals (4). The majority (58%) had a rheumatologist as head physician. All centers used Iloprost: a single monthly administration was the most common treatment (75%). The cycle lasted 1 [IQR 1-2] days with a 0.5-2.0 ng/Kg/min dose according to the drug tolerance of the patients. There were overall 68 spots (beds, reclining armchair, or simple armchair); 2.0 [1.5-4.0] patients were able to receive Iloprost at the same time. University Hospitals had more physicians at their disposal than local hospitals but less paramedic personnel (respectively: 1.8 vs 1.2 physicians, 1.5 vs 2.1 nurses). Conclusions: These observations were in line with the majority of previous studies reporting different regimens, comparing similar (but not identical) dose and schedule administration, however, despite differences being at times substantial, no standard infusion method is yet available.